Apple pomace as a potential valuable resource for full-components utilization: A review. (20th December 2021) - Zhang, Fan; Wang, Tao; Wang, Xin; Lü, Xin
Abstract: Apple pomace (AP), the by-products generated from apple processing industries, is a favorable resource possessed the characteristics of high nutritional component, which are of great interest in its utilization. It is urgent to dispose AP efficiently and eco-friendly in case of unnecessary waste and environmental pollution of producing fetor or harmful substance with landfill. This review provides valorization strategies for recycle AP, discusses the current utilization modes and analyzes the development tendency of different AP utilization methods through summarizing literatures related with the current situation of apple, apple processed products and the utilization of AP roundly. In line with literatures, the application of AP could be divided into two categories: being applied in conventional ways and being applied in acquiring high-value products. The former included directly as an additive in animal feed or elementary fermentation conversion to compost or produce nutrition enhancement, and the latter included functional ingredients (carbohydrates, phenolic compounds and pentacyclic triterpenes) extraction or fermentation conversion to produce high-value products (enzymes, organic acid, pigment, biofuels), some flaws limited the AP utilization were described as well. However, the techno-economic assessment and life cycle assessment are necessary for commercial application of AP at the optimal technologies, which is best promising for reducing economic cost and environment pollution. The discussion about the limitation and future tendency of every utilization mode is concluded at the last paragraph of every section owing to the lack of in-depth and comprehensive research of AP valorization. More than that, the concept of full-component utilization to enhance economic efficiency and utilization ratio of AP as much as possible is proposed at the end, effectively establish the foundation of acquiring sustainable food products and improve the value-added of wastes. Graphical abstract: Image 1 Highlights: High-value products obtained is a promising way for apple pomace utilization. Pretreatment and co-culture fermentation should be applied in apple pomace fermentation. Screening of novel strains and enzymes about apple pomace utilization is necessary. A new point of full-component utilization was proposed for apple pomace utilization.